2007
DOI: 10.1037/0022-006x.75.1.43
|View full text |Cite
|
Sign up to set email alerts
|

The drinking partnership and marital satisfaction: The longitudinal influence of discrepant drinking.

Abstract: The objective was to determine whether discrepancies between husbands' and wives' past year heavy drinking predicted decreased marital satisfaction over time. Participants were recruited at the time they applied for their marriage licenses (N= 634). Couples completed questionnaires about their alcohol use and marital satisfaction at the time of marriage, and again at their first and second anniversaries. Generalized estimating equation models were used to evaluate the association between discrepancies in husba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
160
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 159 publications
(180 citation statements)
references
References 52 publications
(63 reference statements)
17
160
2
1
Order By: Relevance
“…However, there were no differences across clusters in relationship quality, which is surprising because previous research found that discrepancy was related to more relationship problems, such as lower satisfaction and commitment (e.g., Homish and Leonard, 2007). Perhaps the Add Health measure was inadequate to fully address satisfaction and commitment.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…However, there were no differences across clusters in relationship quality, which is surprising because previous research found that discrepancy was related to more relationship problems, such as lower satisfaction and commitment (e.g., Homish and Leonard, 2007). Perhaps the Add Health measure was inadequate to fully address satisfaction and commitment.…”
Section: Discussioncontrasting
confidence: 41%
“…First, the current study explored data from both couple members using a nationally representative sample rather than community samples (Homish and Leonard, 2007) or using only one couple member (Wiersma et al, 2009). The Add Health followed the same individuals from young adulthood into adulthood, which allowed the current study to examine the association of individuals' drinking in earlier types of romantic relationships with their adult behaviors.…”
Section: Strengths and Weaknessesmentioning
confidence: 99%
“…However, with these exceptions, they did not experience more health problems or defi cits in family and social functioning. Thus, these spouses may have formed a somewhat uneasy "drinking partnership" (Homish and Leonard, 2007) with their mates and engaged in moderate to heavy alcohol consumption as a normative social activity. Consistent with this idea, at the 10-year follow-up, this group of spouses continued to drink more heavily and to report more friends' approval of drinking than spouses of problem-free drinkers did.…”
Section: Spouses Of Older Adults With Continuing Late-life Drinking Pmentioning
confidence: 99%
“…Aside from married couples' concordance in these areas of functioning, there is very little information about the health, family, and social adaptation of spouses of late-life problem drinkers. Studies of younger couples have shown that a partner's heavy drinking and alcohol-use problems may be associated with high levels of marital confl ict and a relative lack of spousal support (Homish and Leonard, 2007;Keller et al, 2009;McLeod, 1993).…”
Section: Functioning Among Spouses Of Late-life Problem Drinkersmentioning
confidence: 99%
“…However, it is still unclear when and for whom effects will be negative versus positive. Drinking effects are more negative when couple members drink relatively heavier compared with lighter amounts (Fisher et al, 2005;Levitt and Cooper, 2010) and when partners drink dissimilar compared with similar amounts (Homish and Leonard, 2007;Levitt and Cooper, 2010;Mudar et al, 2001). Beyond effects of quantity consumed, the drinking context appears to be especially important for relationship functioning.…”
Section: Relationship Drinking Contexts and Relationship Functioningmentioning
confidence: 99%